Emotion Regulation in Psychology in Students - Enny Fitriani; Nurasyah; Johannes; Rini Fadhillah Putri (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to find out how students' emotional regulation is studied in psychology. The period of emotional development of students in their teenage years is a transitional period that is very vulnerable and requires guidance to be able to control emotions. Emotions are a very dangerous mental disorder. We will discuss several important aspects, including the types of emotion regulation strategies commonly used by students, campus environmental factors that influence emotion regulation, and the impact of emotion regulation on students' psychological well-being and academic achievement. Students often face complex academic, social, and emotional stress in the campus environment, so their ability to manage their emotions is critical to their well-being and academic success. The method used in this research is a qualitative descriptive method. The subjects of this research were students at the Indah Medan College of Health Sciences. The results of the analysis using observation techniques. Through this research, it is hoped that there will be a better understanding of the role of emotional regulation in students' lives, as well as practical implications for the development of coaching and intervention programs in higher education environments.